Antioxidant and antimicrobial effects of blackberry, black chokeberry, blueberry, and red currant pomace extracts on beef patties subject to refrigerated storage - Babaoğlu, Ali Samet; Unal, Kubra; Dilek, Nazik Meziyet; Poçan, Hatice Berna; Karakaya, Mustafa (Meat science, 2022)
This study evaluates the physicochemical and microbiological properties and sensory parameters of beef patties formulated with black chokeberry (B1), blackberry (B2), red currant (B3) and blueberry (B4) pomace water extracts during refrigerated storage over 9 days. The berry pomace extract treatment significantly decreased the TBARS numbers of the samples (P < 0.05). The lowest total carbonyl content was determined in the groups of B1 and B3 on the 6th day (P < 0.05). The berry pomace extract treatment did not affect the lightness values of the samples (P > 0.05). Beef patties including berry pomace extracts had lower coliform bacteria counts than the control patty C with no extract (P < 0.05), except for day 9. The results suggest that water extract of black chokeberry pomace may be a promising natural preservative among different berries' pomace extracts to improve oxidative stability and increase the microbiological quality of beef patties during refrigerated storage. •Black chokeberry pomace extract had the highest total phenolic contents.•Blackberry pomace water extract had more effective for delaying lipid oxidation.•Berry pomace extracts decreased the TMAB, TPAB and coliform counts of patties.•Total carbonyl contents were significantly affected by using berry extracts.